Çocuk hakları perspektifinden Güney Avrupa ülkeleri ve Türkiye'de çocuk yoksulluğu - Kaya, Sefa (My University, 2025)
Çocuklar, görece yakın bir tarihte hak sahibi bireyler olarak kabul edilmiştir. ÇHS'nin kabul edilmesinden yaklaşık 35 yıl sonra çocuk yoksulluğu, çocuk işçiliği ve sömürüsü, sosyal eşitsizlikler vb. sorunlar görülmektedir. Çocuk yoksulluğu, çocuklar ve toplum için olumsuz etkilere sebep olabilecek en önemli sosyoekonomik sorundur. Bu araştırmanın konusu, çocuk hakları ve refah rejimleri çerçevesinde Güney Avrupa devletleri ve Türkiye'de çok boyutlu çocuk yoksulluğunun analiz edilmesidir. Temel amacı, çocuk ve çocukluk kavramları ile çocuk hakları yaklaşımı ve refah rejimi yaklaşımı çerçevesinde çocukların erişim konusunda eksiklikler yaşadığı haklar ile çok boyutlu yoksulluk ilişkisini açıklayabilmektir. Bu çalışmanın yöntemini, betimsel yaklaşım çerçevesinde yürütülen kavramsal ve tarihsel araştırma, belge taraması ve karşılaştırma tekniği oluşturmaktadır. Seçilen ülkelerde çocuk ve aile politikaları ve yoksulluk göstergeleri de analiz edilerek teori ile uygulama bütünlük içinde tartışılmaktadır. Bu çalışmada, çocuk yoksulluğuna ilişkin sosyal transferler, ebeveyn izinleri ve erken çocukluk müdahaleleri politikaları ile yoksulluk yaşanan alanlardan maddi durum, eğitim, sağlık, ev ve konut, çevre ve güvenlik/ risk boyutlarına odaklanılmaktadır. Bu kapsamda Avrupa Komisyonu, OECD, EUROCHILD, UNICEF, EUROSTAT vb. kuruluşların ve ulusal kurumların raporları ve verileri kullanılmaktadır. Yapılan analiz sonucunda yoksunluk alanları ve politika yaklaşımlarına ilişkin tespit edilen açıkların giderilmesi amacıyla Çok Boyutlu Yoksulluk Temelinde Çocuk Hakları Gerçekleştirme Model Önerisi ve Model Uygulaması Önerisi literatür ve politika yapıcıların değerlendirmesine sunulmaktadır.

The recognition of children as rights-holders represents a relatively recent development. Despite the 35 years that have elapsed since the adoption of the United Nations Convention on the Rights of the Child (UNCRC), issues such as child poverty, child labour, exploitation, and broader social inequalities persist. Of these challenges, child poverty is widely regarded as the most critical socio-economic issue facing children. It is recognised for its detrimental impacts on both individual children and society at large. The present study focuses on the analysis of multidimensional child poverty in Southern European countries and Türkiye within the frameworks of children's rights and welfare regime theory. The primary objective of this study is to elucidate the correlation between multidimensional poverty and the rights to which children are deprived within the conceptual framework of children and childhood, the children's rights approach, and the welfare regime approach. The methodology of this research consists of conceptual and historical analysis, employing document review and comparative methods within a descriptive research design. The study analyses child and family policies, as well as poverty indicators, across a number of selected countries. Furthermore, it engages with the integration of theoretical frameworks with actual policy implementation. The study places particular emphasis on social transfers, parental leave, early childhood intervention policies, and the multiple dimensions of deprivation, including material conditions, education, health, housing, environment, and exposure to risk. A broad range of data and reports has been utilised from both international organisations -such as the European Commission, OECD, EUROCHILD, UNICEF, and EUROSTAT- and national institutions. Based on the findings, two proposals are presented to the academic and policy-making communities: a Model for Realising Children's Rights through a Multidimensional Poverty Framework and an associated Implementation Model. These proposals aim to address the deficiencies observed in current policy approaches and areas of deprivation, offering strategic direction for more effective interventions.
Child poverty in southern European Countries and Turkey from a child’s rights perspective
Keywords: Avrupa Birliği Ülkeleri; Child Poverty; Child Rights; Children; Children's rights; Çocuk; Çocuk hakları; Çocuk Yoksulluğu; Çocuklar-- Hukuki durum, kanunlar, vb; Çocukluk Anlayışı; Çok Boyutlu Yoksulluk; European Union Countries; Güney Avrupa; Legal status, laws, etc; Neoliberalism; Neoliberalizm Child; Poverty; Refah Rejimi; Southern European; The Conceptions of Childhood; Turkey; Türkiye; Walfare Regime; Yoksulluk